Antidepressants Use Among Pregnant Women in Denmark From 2001 to 2023: A Population‐Level Drug Utilization Study - Andersen, Anne‐Johanne; Enevoldsen, Kasper Nørlund; Enevoldsen, Anne Sophie; Gram, Erika B.; Damkier, Per (Basic & clinical pharmacology & toxicology, 2025)
ABSTRACT We evaluated trends in antidepressant use among pregnant women in Denmark from 2001 to 2023, comparing them with a matched comparison group from the general population. Data from the Danish Health Data Authority were used to assess annual antidepressant prescription redemption rates per 1000 pregnancies, with a focus on total antidepressant use, selective serotonin reuptake inhibitors (SSRIs) and serotonin noradrenaline reuptake inhibitors (SNRIs). Antidepressant use among pregnant women increased fivefold in the study period. In the comparison group, use increased 2.3‐fold. After a decline following 2011, antidepressant use among pregnant women began to rise again in 2019, driven primarily by sertraline, which accounted for 76% of prescription redemptions in 2023. Other drugs such as escitalopram, duloxetine, mirtazapine and amitriptyline showed modest increases, while the use of most other antidepressants declined or stabilized. This upward trend likely reflects the influence of updated clinical guidelines and greater clinical acceptance of antidepressant use during pregnancy. Our findings emphasize how prescribing practices are sensitive to shifts in public discourse and guideline revisions, highlighting the importance of ongoing pharmacovigilance in managing maternal mental health. Plain Language Summary We evaluated antidepressant use in pregnancy in Denmark from 2001 to 2023. Antidepressant use in pregnancy increased fivefold, compared with a little more than twofold in the comparison group. After a decline around 2011, use rose again from 2019, mainly due to sertraline, which by 2023 was the most prescribed antidepressant. We observed minor increases for a few other antidepressants, but most remained stable or declined. These latter trends likely reflect updated treatment guidelines and growing acceptance of antidepressant use in pregnancy.